Analisis Minat Belajar Matematika Siswa Sma Pada Materi Program Linier Berbantuan Aplikasi Geogebra - Ernawati Ernawati; Leni Nurhayati; Wahyu Setiawan (Journal on Education, 2019)
This study aims to analyze students' interest in learning mathematics in linear program material using the geogebra application. The research method used is descriptive analysis. The population in this study were private high school in West Bandung Regency and the sample taken was class XI students of Leppesa 2 Cililin high school, totaling 25 people, 13 male and 12 female. The instrument used was a statement questionnaire with indicators of student interest in learning consisting of 20 statements. Based on the results of data analysis obtained an overall percentage of 51.39% which shows that most of the students have an interest in learning mathematics in linear program material assisted by geogebra ICT media.